2014
DOI: 10.3390/ijms15046046
|View full text |Cite
|
Sign up to set email alerts
|

PSMA, EpCAM, VEGF and GRPR as Imaging Targets in Locally Recurrent Prostate Cancer after Radiotherapy

Abstract: In this retrospective pilot study, the expression of the prostate-specific membrane antigen (PSMA), the epithelial cell adhesion molecule (EpCAM), the vascular endothelial growth factor (VEGF) and the gastrin-releasing peptide receptor (GRPR) in locally recurrent prostate cancer after brachytherapy or external beam radiotherapy (EBRT) was investigated, and their adequacy for targeted imaging was analyzed. Prostate cancer specimens were collected of 17 patients who underwent salvage prostatectomy because of loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 62 publications
1
41
0
1
Order By: Relevance
“…In early studies using 99m Tc-labeled-BnR-agonists[133,178,179] involving 4–10 patients with proven/suspected prostate-cancer, specific-uptake by the probe was seen in 25% in one study[133] and in 100% of patients in the other two studies[178,179], for both the primary tumor and lymph node metastases(Table 1). A recent study[180] investigated the expression of various proteins used for imaging prostate-cancer or reported to be overexpressed and potentially useful for imaging (PSMA, EpCAM, VEGF and GRPR), in recurrent prostate-cancer in patients after surgery or radiotherapy. This study[180] in 17 patients prostate-cancer samples found in the tumor the PSMA; EpCAM; VEGF; GRPR positivity was; 100; 82; 82;100% and in the surround nontumor, stromal tissue it was 0 ;0; 0; 100%.…”
Section: Bn-peptides-bnr: Prostate-cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In early studies using 99m Tc-labeled-BnR-agonists[133,178,179] involving 4–10 patients with proven/suspected prostate-cancer, specific-uptake by the probe was seen in 25% in one study[133] and in 100% of patients in the other two studies[178,179], for both the primary tumor and lymph node metastases(Table 1). A recent study[180] investigated the expression of various proteins used for imaging prostate-cancer or reported to be overexpressed and potentially useful for imaging (PSMA, EpCAM, VEGF and GRPR), in recurrent prostate-cancer in patients after surgery or radiotherapy. This study[180] in 17 patients prostate-cancer samples found in the tumor the PSMA; EpCAM; VEGF; GRPR positivity was; 100; 82; 82;100% and in the surround nontumor, stromal tissue it was 0 ;0; 0; 100%.…”
Section: Bn-peptides-bnr: Prostate-cancermentioning
confidence: 99%
“…A recent study[180] investigated the expression of various proteins used for imaging prostate-cancer or reported to be overexpressed and potentially useful for imaging (PSMA, EpCAM, VEGF and GRPR), in recurrent prostate-cancer in patients after surgery or radiotherapy. This study[180] in 17 patients prostate-cancer samples found in the tumor the PSMA; EpCAM; VEGF; GRPR positivity was; 100; 82; 82;100% and in the surround nontumor, stromal tissue it was 0 ;0; 0; 100%. This led the authors to conclude that to evaluate recurrent prostate-cancer after therapy, GRPR should not be a target for bio-imaging and that,PSMA, EpCAM; VEGF should be considered[180].…”
Section: Bn-peptides-bnr: Prostate-cancermentioning
confidence: 99%
“…Prostate speci ic membrane antigen (PSMA) is a membrane bound protein that is more avidly expressed in primary as well as in metastatic prostate cancer [4][5][6]. Extensive research is going on to develop PSMA ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate specific membrane antigen (PSMA) is a membrane bound protein that is more avidly expressed in primary as well as in metastatic prostate cancer. [3][4][5][6] This transmembrane protein has a large extracellular domain and a small intracellular domain and thus provides a promising theranostic target for prostate cancer imaging and therapy. 3 Extensive research is going on to develop PSMA ligands.…”
Section: Figurementioning
confidence: 99%